Para além da greve: o diálogo ítalo-brasileiro para a construção de um direito ao pluralismo político da classe-que-vive-do-trabalho - Flávia Souza Máximo Pereira (2017)
This theoretical comparative research between Italy and Brazil aims to be an opened debate, since its main objective is to establish a constant dialogue among the Legal Science and those heterogeneous individuals who live from their own labor and are protagonists of dynamic forms of struggle against flexible instruments of exploitation in the contemporary capitalism. As labor moves outside the factory walls, becomes more difficult to maintain any working day measurement and therefore separate the private time from the production one, because those who live by selling their own labor force produce in all their generality, everywhere, all the time. As a result, the working class in contemporary capitalism is not constituted only by the mass-worker, unionized, employee at an industrial national company organized according to the taylorism-fordism system. When the logic of the valorization of value through the locus of human labor transcends to places beyond the factory production space, intersectional subalternities are revealed, requiring the reconfiguration of collective struggles frameworks, as well as its interests to be defended and its forms of action. In this place of ontological construction, the class-that-lives-from-labor appears as a constituent power, expressing their critical content in new forms of collective struggle that aim to be more useful in contemporary capitalism than strike, which in its traditional format is still attached to the cleavages of modernity. In opposition to corporate legal relations, which changed quickly to promote the dismantling of labor rights, the right to strike remained in the background in terms of legal adaptation: it did not follow the "flexible" paradigm and therefore did not become an effective or efficacious legal instrument able to protect new forms of struggle. As result of this axiological legal gap, this thesis proposes the acknowledgment of a right to struggle of the class-that-lives-from-labor (and not a mere freedom, according to Piero Calamandreis classification) to become possible to convert these social-labor demonstrations in a legitimate legal instrument, immune to criminal and civil repression, which will be able to change the balance of power and inequality. This study aimed to understand whether there was space in the Italian-Brazilian concept of right to strike to overcome such axiological legal gap, in other words, if was possible to transpose the social-labor conflicts to the legal locus of the right to strike without blocking the configurations of the political struggle; or if it was necessary to seek other legal places in the Italian-Brazilian system for an effective protection of workers conflict. This research analyzed the contemporary concept of the right to strike in the private sector through the study of the doctrine, case law and legislation of Italy and Brazil in order to verify if it was possible to recognize other senses to the right to strike which could promote the legal protection of these new forms of struggle without the neutralization of its political content, according to Jacques Rancière's theory. These renewable struggle forms of the class-that-lives-from-labor represent democratic methods of political connection and therefore they can not be transposed into juridical places filled with obstacles created by modernity cleavages which are able to block their dynamic potential of citizenship that is crucial for a plural democracy. Due to these obstacles still featured in Italy and Brazil, this thesis proposes the legal recognition of the political struggle in other juridical places that are diverse from the right to strike, through the acknowledgement of the right to political pluralism of the class-that-lives-from-labor, which manifests itself in various legal provisions, such as the right to occupy, the right to demonstrate, the right to the city, the right to transnational collective action, which enable anyone who-lives-from-their-labor to be an active part of the process of Laws institutional definition, outstanding other possible legal-political logics of the Constitution and legislation, which should always be opened to dispute, in order to keep alive the transformation as role of Law as a Social Science, allowing other democracies.